SELECTIVITY OF DRIFT GILLNET IN THE WATERS OF NUSANTARA SUNGAILIAT FISHING PORT BANGKA BELITUNG PROVINCE - Ayu Nita Ervina Tambunan; Isnaniah Isnaniah; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe selectivity of the fishing gear is defined as the ability of the fishing device to obtain specific fishing targets by type and size during the capture process and allow all unwanted by-catch catches to be passed unscathed (FAO, 1995). The purpose of this study was to find out the selectivity of the mesh size and the composition of the catch of drift gillnets in PPN Sungailiat. The result of this research is a drift gillnet with a mesh size of 8.89 cm caught tuna with a fork length range of 32 - 45.7 cm and the highest catch ratio was caugth at fork length (L). = 37.7 cm with Sa = 0.999289326.Meanwhile, mesh size of 10.16 cm caught tuna with a fork length range of 36.6 - 50.3 cm and the highest catch ratio was caught at fork length (L) = 43.3 cm with Sb = 0.999974108.So that drift gillnet with a mesh size of 10.16 cm are more selective than drift gillnet with a meh size of 8.89 cm,because the L value is greater and the S value is closer to 1. As well as catching more large fish that are fit to catch (≥ 40 cm).Keywords : Fishing Gear; Selectivity; Sungailiat; Drift Gillnet